Jaringan Aktor Dalam Pemberdayaan Masyarakat Pada Program Kota Tanpa Kumuh (KOTAKU) Di Kelurahan Pasar II Kecamatan Prabumulih Utara Kota Prabumulih Provinsi Sumatera Selatan - Purna Irawan; Alfitri Alfitri; Ardiyan Saptawan (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2019)
This research purpose to seeing how the network of actors in community empowerment Kota Tanpa Kumuh (KOTAKU) programs. The research uses descriptive qualitative methods, which discuss the matter of exploration and clarification of social phenomena or challenges by designing describing variables relating to the problem and unit discussed. Interviews were conducted with informants who were program actors or actors, both government, private, program implementers and the community. The results of the research are the individual relations between actors in empowerment in the Kota Tanpa Kumuh (KOTAKU) programs are still symmetrical, and equality with strong ties and there are also weak ties between actors. Relations between institutions are asymmetrical with dominant actor ties in the form of work relations and weak ties in the form of kinship. Factors that become obstacles in community empowerment in the implementation of Kota Tanpa Kumuh (KOTAKU) programs are delays in the disbursement of investment fund assistance (BDI), input competency facilitators in various empowerment fields, as well as the sectoral ego interests of each community empowerment actor. The delay in disbursing BDI allocations has implications for the constraints of the development and empowerment process. Input from facilitators has become an obstacle in developing empowerment and facilitation methods. The interests of sectoral egos cause ineffective division of roles so that potential in each sector cannot be fully benefited